The ultraviolet radiation environment of Antarctica - McMurdo Station during September-October 1987 - Lubin, Dan; Frederick, John E.; Krueger, Arlin J. (1989)
Daily data from the Nimbus-7 TOMS were combined with a model of atmospheric radiative transfer to compute the time evolution of ultraviolet irradiance, at wavelengths from 290 to 350 nm, incident on McMurdo Station during September-October 1987. Large changes in column ozone occur as the polar vortex moves over the site. This is accompanied by correspondingly large variations in UV radiation at the earth's surface. At a wavelength near 305 nm, the irradiance in early October exceeds values appropriate to an unperturbed ozone layer by a factor of 5-6. As December 21 approaches, the noontime UV irradiance increases, irrespective of changes in ozone.